Insights from novel word learning: Error analysis and its relevance in understanding fast versus slow mapping - Abhishek BP; Spoorthi Jain (Journal of Child Language Acquisition and Development)
Novel word learning refers to the process of learning words. The words are assumed to be acquainted even after a short exposure and this phenomenon is termed as fast mapping. Some proponents believe that the new word learnt as a consequence of new word learning is momentous and the word may not be transferred to the lexicon if the word is not rehearsed and this strategy involving conscious learning is termed as slow mapping. The present study was carried out with the aim of carrying out of error analysis on data involving fast and slow mapping. 20 participants were divided into two sub groups of 10 each. The first method was exposed to lexical method of teaching while the second group was exposed to slow mapping. Participants performed well with slow mapping but the errors were more with this method compared to fast mapping.